PERANAN BUDAYA ORGANISASI DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU - Ujang Tholib; Pauzan Haryono (LPPM Universitas Islam 45, 2023)
This research aims to determine the role of organizational culture at SMP Daya Utama Bekasi City. Organizational culture in schools is a factor that can encourage organizational success in the teaching and learning process. Successful learning must be supported by a strong organizational culture in implementing the teaching and learning process. This research applies qualitative research methods that use a pedagogical approach. The data source, namely primary data, comes from interviews with school principals and teachers at Daya Utama Middle School, Bekasi City. Meanwhile, secondary data taken from documents supports the research results. The instrument used to collect data was in-depth interviews. Observation and documentation by determining and selecting informants as data sources, analyzing data, interpreting data, and drawing conclusions. The results of the research show that efforts that can be made to increase teachers' professional competence are related to difficulties in delivering teaching material in the form of mastering teaching material easily. Teachers need to read more, study, explore and review teaching materials in textbooks and student books by having lots of books. references that can support learning activities in class and the role of teachers must be given a teaching load according to their expertise.